Perancangan Dan Analisis Statik Sistem Rangka Mobil Hemat Energi â€œAsykar Hybrid Universitas Riauâ€ - Laka, Oktafatahna; Nazaruddin, Nazaruddin; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Frame is the very important of vehicle. Design of the right frame will provide optimal results between the level of security and the size of the construction. To get an energy-efficient car, it is necessary to design a car frame that fits your needs. From the design carried out based on the body shape of the vehicle, a construction structure of the Asykar Hybrid is Monocoque type frame by using a profile of rectangular hollow section by 30 mm x 50 mm x 2 mm and angel L section 50 mm x 50 mm x 3 mm and dimensions overall frame with a length of 2456 mm x width 932 x height 920 mm. Static analysis calculate by Autodesk Inventor 2018 Student Version software which produces a Principle Stress on the main stem of 46.99 MPa and displacement of 6.005 mm. The results of the manual calculation of the main Principle Stress are 56.94 MPa with a Shear of 28.47 MPa. Safety factor of 4.39 by using Carbon steel ST 37 material. So it was concluded that the framework of energy-efficient cars is safe to use.Keywords: Frame, Principle Stress, Deformation, Energy Saving